Comparison of suture button fixation and syndesmotic screw fixation in the treatment of distal tibiofibular syndesmosis injury: A systematic review and meta-analysis. (December 2018) - Xie, Linzhen; Xie, Huanguang; Wang, Jinwu; Chen, Chunhui; Zhang, Chuanxu; Chen, Hua; Zheng, Wenhao
Abstract: Purpose: This systematic review and meta-analysis was performed to investigate the outcomes of syndesmotic screw fixation versus suture button fixation in the treatment of distal tibiofibular syndesmosis injury from the current literature. Methods: The electronic literature database of PubMed, Embase, and Cochrane library were searched in August 2018. The data on medial clear space, tibiofibular clear space, tibiofibular overlap, American Orthopaedic Foot and Ankle Society (AOFAS) scores and complications (including wound infection, local irritation or discomfort, screw loosening and screw breakage) were extracted. Stata 14.0 software was used for our meta-analysis. Results: A total of 11 studies including 5 randomized controlled trials (RCTs) and 6 cohort studies met our inclusion criteria. This meta-analysis showed that there was no significant difference between the two groups regarding medial clear space (P = 0.54), tibiofibular clear space (P = 0.23) and tibiofibular overlap (P = 0.88) postoperatively. However, the present meta-analysis demonstrated that the suture button fixation group had significantly higher AOFAS scores than the syndesmotic screw fixation group at 3rd, 6th, 12th and 24th months postoperatively (P = 0.001, P = 0.006, P = 0.000 and P = 0.049 respectively). Besides, the time to full weight bearing in the suture button fixation group was significantly earlier than that in the syndesmotic screw fixation group (P = 0.000). As for the complications, the suture button fixation group had a lower rate of post-operative complication (screw loosening and screw breakage) compared with the syndesmotic screw fixation group (P = 0.048 and P = 0.000 respectively). Conclusion: Our meta-analysis suggested that suture button fixation could achieve significant higher AOFAS scores with a lower rate of postoperative complications and earlier time to full weight bearing in distal tibiofibular syndesmosis injury. More RCTs are required for further research. Highlights: Suture button fixation had significantly higher AOFAS scores than syndesmotic screw fixation. Suture button fixation had earlier time to full weight bearing than syndesmotic screw fixation. Suture button fixation had lower rate of post-operative complication compared with syndesmotic screw fixation. No significant differences were found regarding the radiographic outcomes between the groups. Suture button fixation is superior to syndesmotic screw fixation with better outcomes.